Percepción del cliente en la hostería Casa Grande, de la ciudad Balsas, cantón Balsas - Robles Feijoo, Dayana Elizabeth (2024)
The Casa Grande Inn is located in the province of El Oro, canton Balsas, in the streets Eliseo Romero and October 4, which provides lodging, food, events and recreation services. For the development of this research project, the perception of the clients was evaluated, taking as main objective; to identify the perception of the tourist services in the Inn, in which two specific objectives were deployed; To measure the perception of tourism services in the Casa Grande Inn and to elaborate a service improvement plan for the Casa Grande Inn in Balsas canton. For the first objective, we used a business information gathering form to make a diagnosis of the inn, a check list to verify whether or not it meets the requirements for the operation of the inn, a survey based on the Servqual model, which contains 31 items, 9 general information questions to find out if it meets the requirements for the operation of the inn, a survey based on the Servqual model, which contains 31 items: 9 questions of general information to know the profile of the customer staying at the inn and 22 questions of the dimensions (reliability, sensitivity, security, empathy, tangible elements), an external analysis of the company was performed using the Pestel, then the Foda matrix and cross Foda were performed to obtain the strategies. In the second objective, an improvement plan adapted to MINTUR was developed, based on the strategies extracted from the crossed SWOT. Among the results, an improvement plan focused on the services of the inn was obtained. In conclusion, an evaluation of the quality of the service offered by the inn was carried out, in which the existing problems were determined by dimensions, therefore, it was possible to make an improvement plan focused on the services, which will help to provide solutions to the shortcomings perceived by the client in the services offered, in the same way to improve the quality of service and customer perception.